1999
DOI: 10.1111/j.1348-0421.1999.tb02456.x
|View full text |Cite
|
Sign up to set email alerts
|

Borna Disease Virus Infection in Two Family Clusters of Patients with Chronic Fatigue Syndrome

Abstract: A high rate of Borna disease virus (BDV) infection has been demonstrated in patients with chronic fatigue syndrome (CFS). Herein, we focused on BDV infection in two family clusters of patients with CFS: a father, mother, two sons and one daughter (family #1); and a father, mother, two daughters and one son (family #2), All members, except for the elder son in family #1 and the father and son in family #2, were diagnosed with CFS. The results supported that all the family members with CFS were infected with BDV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 43 publications
0
8
0
1
Order By: Relevance
“…However, in a classical example of the pitfalls of PCR diagnostics, particularly using nesting methods, BDV was implicated in a wide variety of disorders that included major depressive disorder, bipolar disorder, schizophrenia, chronic fatigue syndrome (CFS), AIDS encephalopathy, multiple sclerosis, motor neuron disease, and brain tumors (glioblastoma multiforme) (75). Following a report of BDV RNA in the blood of more than 50% of CFS subjects, which raised concerns for blood product safety (87,88), we were recruited to pursue a replication study. We found no BDV nucleic acid or specific immunoreactivity in a blinded analysis of well-characterized CFS subjects.…”
Section: Molecular Characterization Of Borna Disease Virus a Novel Nmentioning
confidence: 99%
“…However, in a classical example of the pitfalls of PCR diagnostics, particularly using nesting methods, BDV was implicated in a wide variety of disorders that included major depressive disorder, bipolar disorder, schizophrenia, chronic fatigue syndrome (CFS), AIDS encephalopathy, multiple sclerosis, motor neuron disease, and brain tumors (glioblastoma multiforme) (75). Following a report of BDV RNA in the blood of more than 50% of CFS subjects, which raised concerns for blood product safety (87,88), we were recruited to pursue a replication study. We found no BDV nucleic acid or specific immunoreactivity in a blinded analysis of well-characterized CFS subjects.…”
Section: Molecular Characterization Of Borna Disease Virus a Novel Nmentioning
confidence: 99%
“…In the past decade, BDV RNA, BDV proteins, anti-BDV antibody, and/or infectious virus have been found in the blood, CSF, and/or brains of patients with chronic fatigue syndrome (83,97,98) (46), and patients with various psychiatric disorders (150).…”
Section: Evidence For Bdv-induced Disease In Humans: Possible Clinicamentioning
confidence: 99%
“…In a Japanese study by Nakaya et al the prevalence of BDV p24RNA and antibody in Peripheral Blood Mononuclear Cells (PBMCs) and serum of patients with CFS was 32%, supporting the association between BDV and CFS (19). Some studies suggested a strong association in some cases of CFS (20,21).…”
Section: Contextmentioning
confidence: 94%